Transport and CO2: Productivity Growth and Carbon Dioxide Emissions in the European Commercial Transport Industry - Lisann Krautzberger; Heike Wetzel (Institute of Energy Economics at the University of Cologne (EWI), 2011)
In the last decades transport activities persistently increased in the EU27 and were strongly coupled to growth in GDP. Like most production processes, they are inevitably linked with the generation of environmentally hazardous by-products, such as CO2 emissions. This leads to the question of how to promote a sustainable transport sector that meets both environmental protection targets and economic requirements. In this context, the objective of this paper is to compare the CO2-sensitve productivity development of the European commercial transport industry for the period between 1995 and 2006. We calculate a Malmquist-Luenberger productivity index to investigate the effects of country-specific regulations on productivity and to identify innovative countries. Our results show a high variation in the CO2-sensitive productivity development and a slight productivity decrease on average. Efficiency losses indicate that the majority of the countries were not able to follow the technological improvements induced by some innovative countries.
Keywords: L92; Q47; Q53; Q56; 330; European transport industry; Carbon dioxide emissions; Productivity growth; Malmquist-Luenberger index